Evaluation of Early Retinal Nerve Injury in Type 2 Diabetes Patients Without Diabetic Retinopathy - Jia, Xiuhua; Zhong, Zhijian; Bao, Tiancheng; Wang, Shasha; Jiang, Ting; Zhang, Yanling; Li, Qigen; Zhu, Xiang (Frontiers in Endocrinology, 2020)
Objectives: To investigate the damage to the retinal nerve fiber layer (RNFL) and ganglion cell complex layer (GCL+) in diabetic patients without retinal microangioma and to determine the kind of nerve damage more likely to indicate early injury. Subjects and methods: We included 360 patients (360 eyes) with type 2 diabetes mellitus and 168 healthy volunteers (168 eyes). Patients with retinal microangioma were excluded by fundus fluorescein angiography (FFA). The parameters around the optic disc and macular area were measured by optical coherence tomography (OCT). Results: The peripapillary RNFL thickness was thinner in the temporal (72.98 ± 13.76 μm, P < 0.0001) and inferior (120.71 ± 21.43 μm, P = 0.0103) sectors in patients with no diabetic retinopathy (NDR) compared to healthy controls. The reduction of retinal thickness in the macular region was prominent in the inferior sector in patients (34.74 ± 4.92 μm, P < 0.0001) compared to normal controls. Thinning of GCL+ in the second region of the macular area was significant in patients with NDR compared to normal controls (P < 0.05). However, no difference in the GCL+ and retinal thicknesses of the central macular region was observed between the patients with NDR and healthy controls. Using the 5th percentile (P5) of normal controls as the reference value, we found that the parameters with the highest indices in patients with NDR were the inferior and temporal peripapillary RNFL thickness (13.0%), the inferior RNFL thickness in the macular area (20%), the inferior retinal thickness in the outer ring of the macular area (10.8%), and the inferior GCL+ thickness in the macular area (10.6%). The GCL+ and RNFL thicknesses in the central macular area accounted for the smallest proportion in P5 of normal controls (3%). Conclusions: Retinal nerve injury can occur in patients without retinal microangioma. The inferior RNFL in the macular area and the inferior and temporal peripapillary RNFL were most sensitive to glucose damage. These areas might be associated with early detection of diabetic retinopathy (DR) as they are more likely to indicate early damage.